Characterization of Lineage-Traced Sftpc progenitor cells in the Bronchi (LTS-B) during lung homeostasis and after injury in mice - Noori, Afshin; Justus Liebig University Giessen (My University, 2025)
This dissertation investigates a novel progenitor population in the lung that was identified through Sftpc lineage-tracing experiments. This population resides in the bronchi and is distinct from classical AT2 cells. Although AT2 cells have long been considered the primary source of alveolar regeneration, lineage-tracing studies using SftpcCreERT2 mice combined with Tomatoflox and SftpcGFP reporters revealed an additional population of tdTom⁺ GFP⁻ cells localized to the bronchial epithelium. This population is termed Lineage-Traced Sftpc Cells in the Bronchi (LTS-B). These cells represent approximately 1.6% of epithelial cells and occupy a unique niche on the apical side of bronchial smooth muscle. Interestingly, transcriptomic analysis revealed a hybrid identity with reduced AT2 signatures, enrichment of ciliated and club cell markers, activation of PI3K/Akt signaling, and reduced Fgfr2b signaling. These findings establish LTS-Bs as a distinct progenitor pool. Further analysis using single-cell RNA sequencing revealed heterogeneity within this population and identified two distinct subtypes of LTS-B based on transcription. One cluster expresses FoxJ1, Tpp3, and markers, resembling ciliated cells. The other cluster expresses Sftpc and Abca3, resembling alveolar cells. This dual identity underscores their transitional nature, linking airway- and alveolar-like fates. To study epithelial injury and repair dynamics, precision-cut lung slices (PCLS) were used in conjunction with in vivo naphthalene-induced injury. The PCLS model reproduced hallmarks of acute epithelial stress, including rapid declines in Sftpc, Epcam, and Scgb1a1 expression. This is followed by a partial recovery of mesenchymal and growth factor markers, such as Fgf10 and Acta2. This reflects the initiation of repair programs. These results validate PCLS as a powerful ex vivo system for studying progenitor cell behavior. In this context, LTS-B cells expanded in response to injury, both in vivo and ex vivo. Live imaging revealed their motility and migration from the bronchi toward the alveolar area. Next, transcriptomic profiling revealed that LTS-B cells, upon 8 days of PCLS culture, adopt an alveolar differentiation intermediate (ADI)-like state, positioning them as transitional progenitors. Treating PCLS with FGF10 and CHIR99021 partially induced LTS-B differentiation into SftpcGFP⁺ cells, suggesting their potential to contribute to alveolar lineages. Comparative analyses revealed that LTS-Bs are distinct from other progenitor pools, including bronchioalveolar stem cells (BASCs), lineage-negative epithelial progenitors (LNEPs), and basal or club cell populations. Instead of being a variant of these cells, LTS-Bs constitute an unrecognized progenitor pool with a unique identity, localization, and behavior. Preliminary evidence from human idiopathic pulmonary fibrosis (IPF) samples suggests that LTS-B-like cells may exist in humans as well, sharing transcriptional features with the murine population. These findings raise the possibility that LTS-Bs participate in both physiological regeneration and maladaptive remodeling during chronic lung disease. In summary, this dissertation identifies and characterizes LTS-B as a rare, bronchi-localized progenitor population that expands during injury and adopts an ADI-like transitional state. Under regenerative cues, this population can partially differentiate toward AT2 fate. Through the establishment of PCLS as a robust ex vivo injury model and the integration of transcriptomic approaches with functional assays, this study broadens our comprehension of epithelial plasticity in the lung and challenges the prevailing notion that AT2 cells are the sole facilitators of alveolar repair. The discovery of LTS-B highlights the complexity of progenitor hierarchies in the lung and opens new avenues for regenerative strategies. If equivalent cells exist in humans, they could be promising therapeutic targets for diseases such as IPF, COPD, and ARDS. However, dysregulated activation of these progenitors could contribute to pathological fibrosis. By identifying LTS-B, this dissertation provides a framework for rethinking epithelial regeneration and emphasizes the importance of exploring diverse progenitor pools in lung biology and disease.
Keywords: ddc:610